Analysis of the Factors Causing Early Marriage in Neniari Village, West Seram Subdistrict, SBB Regency - Kohate, Deslin; Pinoa, Wiclif Sephnath; Leuwol, Ferdinand Salomo (Universitas Pattimura, 2024)
Early marriage, especially below the age of 20, is often triggered by a lack of understanding of negative impacts such as reproductive health issues and limited education. Religion, religious views, and lack of education as well as social pressure, mass media, and local customs play a role in early marriage decisions. The impacts include health problems, interrupted education, and economic issues, as well as an increase in domestic violence and divorce. This study aims to understand the driving factors of early marriage and its impacts, particularly in Desa Neniari, and formulate concrete countermeasures. This descriptive study aims to provide an overview of the impact of early marriage on child rearing patterns within families in Desa Neniari using purposive, internal, and snowball sampling techniques as well as data collection techniques through observation, interviews, questionnaires, and documentation, with data analysis conducted using qualitative descriptive methods. The perspectives of children who marry early in Desa Neniari are influenced by social pressure and financial concerns, while parents view early marriage as a guarantee of a better future for their children, and religion emphasizes physical and mental readiness before marriage, with education playing a crucial role in providing an understanding of the risks of early marriage and developing healthy communication skills for the younger generation.